Coastal engineering conditions of Rayong tidal inlet - Soonthorn Taechavichipisal; Prida Thimakorn; Suphat Vongvisessomjai; Abe, Tetsuo; The Government of Australia (Bangkok : Asian Institute of Technology, 1982)
The significant wave heights and periods are computed using the recorded wind data for a period of eleven years. The computed wave characteristics are used to determine wave statistics and the longshore transport rate. Then the stability of Rayong inlet is investigated. The wind velocity at the Meteorological and U-Tapao Stations was adjusted with increments of 25, 50, 75 and 100% (multiplied by 1.25, 1.5, 1. 75 and 2.0) to determine a reasonable wind data that could be used to determine the wave characteristics and longshore transport. The longshore transport rate at the Rayong River mouth is using estimated the wind data from the Laem Thien, Meteorological and U-Tapao stations. The predominant wind direction in this area is generally south westerly from the available data, but however for the year 1980 the south easterly wind is also significant.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Coastal engineering -- Thailand -- Rayong